Sobre a excitotoxicidade induzida por glutamato em retina embrionária de pinto - Centurião, Fernanda Bossemeyer (2004)
Excitotoxicity refers to the neurodegenerative process initiated by excessive activation of receptors for the neurotransmitter glutamate. This process is one of the most extensively studied processes of neuronal cell death, and plays an important role in many central nervous system (CNS) diseases, including CNS ischemia, trauma, and neurodegenerative disorders. Such excitotoxic cell death seems to involve excessive calcium influx and release from internal organelles, oxyradical production, apoptosis cascades. In this study, we evaluated the effects of three simple diorganyl chalcogenides (diphenyl diselenide, diphenyl ditelluride and diphenyl telluride) and ebselen on glutamate-driven 45Ca2+ influx into chick embryonic retinal cells, as well as their effects on the excitotoxic retina neuronal damage. None of the compounds tested interfered with basal 45Ca2+ uptake. Diphenyl diselenide and diphenyl ditelluride had no effects on glutamate-stimulated 45Ca2+ influx. Diphenyl telluride (100-400 μM) decreased the glutamate-stimulated 45Ca2+ and ebselen (100-400 μM) blocked the glutamate-driven 45Ca2+ influx into chick retinal explants (P < 0.01). The assessment of neuronal injury was made pectrophotometrically by quantification of cellularly reduced MTT (3(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide). Ebselen had no effects on retinal MTT reduction when coincubated with glutamate. However, when ebselen (100 and 400 μM) was coincubated with glutamate and remained in the incubation media until MTT evaluation (24 h after the beginning of incubation), it protected retinas against the decrease in MTT reduction induced by glutamate. These data indicate that besides its capacity to interact with Ca2+ channels, other mechanisms are involved in the neuroprotection afforded by ebselen in this work; possibly its antioxidant properties.